НОМИНАТИВ ФАОЛИЯТНИНГ КОГНИТИВ ВА КОНЦЕПТУАЛ АСОСЛАРИ - Раҳимов, А.А. (SCIENCE and SOCIETY, 2022)
A nomination is an activity based on criteria such as need, action, motivation, goal; it is dictated by the need and inner desire to obtain information about being. This desire, in turn, employs empirical and rational means. The article deals with the cognitive-discursive structure, common to the above diffuse, root and complex words, associated with an ideal cognitive model and nominative meaning based on part-whole relationships.
Keywords: nominative activity; nominant cognitive ability; secondary nomination; concept